“An applied guide to process and plant design” and the epistemology of engineering - Moran, Sean T. (2018)
A significant divergence between the academic study of engineering and its professional practice was identified. This was reported to colleagues and the wider engineering community. Further investigation established that there was no modern textbook which described professional design practice. The most recent textbooks consistent with professional design practice dated from the 1980s. Whilst descriptions of the engineering design process consistent with professional practice were to be found in modern textbooks by engineers from other disciplines, the most widely-used textbooks in chemical engineering tended to describe a kind of ‘process design’ (Douglas, 1988) which was significantly different to its professional counterpart.